Revenge of the dinosaurs. (Economist, 2001)
Reports on a return of interest in central processing mainframes. Topic of firms using spare capacity on their mainframes to run virtual Linux servers; Reasons that companies are experimenting with Linux-on-mainframe; Outlook for distributed computing and for mainframes.